VD_FINDINFO HC / 2009 / 224 vom 31. August 2009 - VD Tribunal cantonal (2009)
DÉCISION DE RENVOI, OBLIGATION D'ENTRETIEN, ENFANT, REVENU, REVENU HYPOTHÉTIQUE | 133 al. 1 CC, 138 al. 1 CC, 145 al. 1 CC, 285 al. 1 CC, 452 CPC